Pelatihan Dasar Ms.Power Point dalam Peningkatan Kreatifitas Presentasi bagi Staf dan Pengajar TKQ-TPQ Kecamatan Tanjung Priok Jakarta Utara - Ummu Radiyah; Astriana Mulyani; Sidik; Imam Budiawan (IKATAN ALUMNI DOSEN MAGANG KEMENRISTEKDIKTI TAHUN ANGKATAN 2017, 2023)
The staff and teachers of TKQ/TPQ Kec. Tanjung Priok in their work activities is not proficient in using technology or applications that make work easier. The problems experienced include not being able to make creative presentation material. Based on the problems experienced by TKQ/TPQ staff and teachers in Tanjung Priok District, basic Ms. Power Point training was carried out to help find solutions to the problems they faced. Ms. Power Point basic training is held to make it easier for staff and teachers to be more able to use and apply technology in the work activities carried out. Ms. Power Point training can also help prepare creative and interesting presentation materials so that teaching and learning activities become dynamic and material can be conveyed by attracting the interest and attention of students and can be timely in disseminating teaching materials. The service method consists of survey stages, training, and evaluation stages. The results of the service show that the TKQ/TPQ staff and teachers, kec. Tanjung Priok can make presentation materials or teaching media that are effective and interesting.